Tantangan Membelajarkan Materi Ilmu Pengetahuan Sosial (IPS) di Sekolah Dasar: Systematic Literature Review (SLR) - Khusnul Khotimah; Toto Nusantara; Aynin Mashfufah (Universitas Negeri Malang, 2024)
Social studies subjects provide students with the chance to make them good citizens. However, teachers face challenges in teaching social studies materials in elementary school. To comprehensively find out the challenges in teaching social studies, the method used in this research is a literature study, with the stages of identification (344 articles), screening (78 articles), and inclusion (19 articles). The keywords used in data collection are challenges and difficulties in teaching social studies in elementary school. Based on the analysis of the articles, it was found that the challenges in teaching social studies materials in elementary schools include difficulties in integrating STEM subjects with social studies, limited time for social studies learning, lack of resources and access to information, lack of funding for facilities and infrastructure, inadequate evaluation and monitoring by the government, challenges for parents in supporting social studies learning, and limited socialization and guidance for teachers. Mata Pelajaran IPS memainkan peran penting dalam kurikulum SD, memberikan siswa landasan pengetahuan yang kuat tentang dunia di sekitar mereka dan menjadikannya sebagai warga negara yang baik. Namun demikian terdapat tantangan yang dihadapi oleh guru dalam membelajarkan materi IPS di SD. Untuk mengetahui secara komprehensif tantangan dalam membelajarkan IPS, metode yang digunakan dalam penelitian ini adalah studi literatur, dengan tahapan identifikasi (344 artikel), screening (78 artikel), dan inklusi (19 artikel). Kata kunci yang digunakan dalam pengumpulan data yaitu tantangan dalam membelajarkan IPS, kesulitan dalam membelajarkan IPS, dan pembelajaran IPS di SD. Berdasarkan analisis artikel diperoleh hasil bahwa tantangan dalam membelajarkan materi IPS di SD antara lain kesulitan dalam mengintegrasikan mata pelajaran STEM dengan IPS, terbatasnya waktu pembelajaran IPS, kurangnya sumber daya dan akses informasi, kurangnya dana sarana dan prasarana, tidak memadainya evaluasi dan monitoring oleh pemerintah, tantangan orang tua dalam mendukung pembelajaran IPS, serta terbatasnya sosialisasi dan bimbingan bagi guru.